The prevalence of obesity documentation in Primary Care Electronic Medical Records: Are we acknowledging the problem? - Mattar, Ahmed (Appl Clin Inform, 2017)
BACKGROUND: Although obesity is a growing problem, primary care physicians often inadequately address it. The objective of this study is to examine the prevalence of obesity documentation in the patient’s problem list for patients with eligible body mass indexes (BMI) as contained in the patients’ electronic medical record (EMR). Additionally, we examined the prevalence of selected chronic conditions across BMI levels. METHOD: This study is a retrospective study using EMR data for adult patients visiting an outpatient clinic between June 2012 and June 2015. International Classification of Diseases, Ninth Revision, (ICD-9) codes were used to identify obesity documentation in the EMR problem list. Univariate and multivariate logistic regression analyses were used. RESULTS: Out of 10,540, a total of 3,868 patients were included in the study. 2,003 (52%) patients met the criteria for obesity (BMI ≥ 30.0); however, only 112 (5.6%) patient records included obesity in the problem list. Moreover, in a multivariate analysis, in addition to age and gender, morbid obesity and cumulative number of comorbidities were significantly associated with obesity documentation, OR=1.6 and OR=1.3, respectively, with 95% CI [1.4, 1.9] and [1.0, 1.7], respectively. For those with obesity documentation, exercise counseling was provided more often than diet counselling. CONCLUSION: Based on EHR documentation, obesity is under coded and generally not identified as a significant problem in primary care. Physicians are more likely to document obesity in the patient record for those with higher BMI scores who are morbidly obese. Moreover, physicians more frequently provide exercise than diet counseling for the documented obese.